2018
DOI: 10.1021/acs.macromol.8b01100
|View full text |Cite
|
Sign up to set email alerts
|

Tetraphenylethene Cross-Linked Thermosensitive Microgels via Acylhydrazone Bonds: Aggregation-Induced Emission in Nanoconfined Environments and the Cononsolvency Effect

Abstract: We studied the aggregation-induced emission (AIE) phenomenon in a nanoconfined environment, where the AIE-active molecule, namely, 1,1,2,2-tetrakis(4-methanoylphenyl)ethane (TPE-4ALD), was held in space via four acylhydrazone bonds within the thermosensitive microgel networks. The thermosensitive microgels, namely N-AH-TPE, were synthesized via the copolymerization of N-isopropylacrylamide (NIPAM) and 4-acylhydrazine-(2-hydroxy-3-(methacryloxypropyl)pyridine hydrochloride (AH monomer) with TPE-4ALD as cross-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…As a result, a great number of organic/polymeric materials containing AIE molecules have been prepared and applied in various fields, such as bioimaging, biosensing, light‐emitting devices, and the drug controlled release materials . However, reports of AIE molecules in thermosensitive nanomaterials are rare . With the aim to develop a novel thermosensitive nanomaterial, this study reported the successful fabrication of temperature‐sensitive liposomes assembled from the component lipids of conventional low‐temperature‐sensitive liposomes (LTSLs) including 1,2‐dipalmitoyl‐ sn ‐glycero −3‐phosphocholine (DPPC), 1,2‐distearoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐N‐[methoxy(polye ‐thylene‐glycol)‐2000] (DSPE‐PEG‐2000) and the newly‐synthesized amphiphilic AIE molecule 4‐oxo‐4‐((1‐(stearoyloxy)‐3‐(2‐(4‐(1,2,2‐triphenylvinyl)phenoxy)acetoxy)‐propan‐2‐yl)oxy)butanoic acid (TPE‐STE).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, a great number of organic/polymeric materials containing AIE molecules have been prepared and applied in various fields, such as bioimaging, biosensing, light‐emitting devices, and the drug controlled release materials . However, reports of AIE molecules in thermosensitive nanomaterials are rare . With the aim to develop a novel thermosensitive nanomaterial, this study reported the successful fabrication of temperature‐sensitive liposomes assembled from the component lipids of conventional low‐temperature‐sensitive liposomes (LTSLs) including 1,2‐dipalmitoyl‐ sn ‐glycero −3‐phosphocholine (DPPC), 1,2‐distearoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐N‐[methoxy(polye ‐thylene‐glycol)‐2000] (DSPE‐PEG‐2000) and the newly‐synthesized amphiphilic AIE molecule 4‐oxo‐4‐((1‐(stearoyloxy)‐3‐(2‐(4‐(1,2,2‐triphenylvinyl)phenoxy)acetoxy)‐propan‐2‐yl)oxy)butanoic acid (TPE‐STE).…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic light scattering, neutron scattering, isotope labeling, and molecular dynamic simulation techniques have been used in the relevant investigation, but the landscape for cononsolvency effect is elusive. Through the aid of an AIEactive fluorescent probe, a clear picture was drawn by a collaborative study and careful analysis of the emission behaviors of the TPE-crosslinked thermo-sensitive microgels in a nano-confined environment [13].…”
Section: Science China Materialsmentioning
confidence: 99%
“…(b) FL spectra of N-AH-TPE microgels in water (H 2 O)/N,Ndimethylformamide (DMF) mixtures with various water molar fractions (χ water ). (c) Plots of emission intensity at maximum emission wavelength of microgels in H 2 O/ethanol (1), H 2 O/methanol (2), H 2 O/DMF (3), H 2 O/DMSO (4), and H 2 O/THF (5) mixtures as a function of water molar fraction.Reproduced with permission from Ref [13]…”
mentioning
confidence: 99%
“…In recent years, development of environmentally responsive polymeric nanogels has attracted tremendous attention because of their wide applications in many advanced fields including disease detection and treatment, drug delivery, sensing, and catalysis taking advantage of their rapid and sensitive responsiveness to minimal changes from environment . Polymeric nanogels with a thermoresponsive property may be one of the most intensively investigated subclasses of responsive nanogels, and many functional monomers are available to prepare thermoresponsive nanogels . Thermoresponsive behavior of polymeric nanogels is mainly determined by the type of thermosensitive polymers, and it can be easily adjusted the polymer composition through adopting homopolymerization or copolymerization of various functional monomers.…”
Section: Introductionmentioning
confidence: 99%